Spremembe rabe tal in socialno-ekonomske sestave prebivalstva na zgornjem gorenjskem - Ferreira, Andreja (Zbornik gozdarstva in lesarstva, 2005)
The paper analyses land-use changes in the Upper Gorenjska region (Slovenia) in the years 1827, 1896, 1979 and 2002. In 1827, 49 % of the land was covered with woods, whereas by 2002 this figure increased to no less than 72 %. While in the 19th century and in the first half of the 20th century only few changesoccurred as far as land-use is concerned, social changes took place after World War II that triggered an extensive process of land greening and afforestation, which in fact still lasts. Particularly interesting are the relations between the changes in land-use and the socio-economic population structure, which show that they are reflected in the region with a considerable delay.
Keywords: agrarna geografija; Gorenjska; prebivalstvo; raba tal; socialno-ekonomska sestava; Upper Carniola